Acoustic Transmission Characteristics of a Eustachian Tube Volitionally Opened in Two Living Subjects. Issue 8 (September 2016) - Amoako-Tuffour, Yaw; Jufas, Nicholas; Quach, Jack; Le, Lisa; Earle, Guy; Kotiya, Akhilesh A.; Bance, Manohar
Abstract : Objective: To assess the acoustic transmission characteristics of the Eustachian tube (ET) in living subjects in verified patent and closed ET states to facilitate the detection and quantification of ET function using acoustic measures such as sonotubometry. Patients: The two subjects in this study had no history of ear disease nor previous ear surgery and were capable of volitionally opening and closing their ET. Interventions: Tympanometry and otologic examinations were used to confirm ET patent and closed states by observing tympanic membrane movement with respiration and by acoustic immitance measurements during forced respiration. A series of 500-ms long chirps containing frequencies from 100 Hz to 10 kHz were introduced into the nasal cavity during both ET states and recorded by microphones in both the contralateral naris and external auditory canal. Main Outcome Measures: Acoustic energy transmission through the ET across the 0.1 to 10 kHz frequency range in the closed state versus the patent state. Results: An increase in acoustic energy transmission occurs across the frequencies of 1 to 4 kHz between the closed and patent ET states, particularly in frequencies below 2.5 kHz. Conclusions: Results support sonotubometry as a potential diagnostic tool for ET dysfunction. Acoustic differences between the ET states manifest as a general increase in transmitted signal amplitude. Characterizing the acoustic properties in the verified patent and closed ET states allows investigators to more reliably interpret sonotubometric tests of ET function. Abstract : Supplemental Digital Content is available in the text